2023
DOI: 10.1002/adfm.202213461
|View full text |Cite
|
Sign up to set email alerts
|

Steric Rooted Multi‐Resonant Thermally Activated Delayed Fluorescent Emitters for Pure Blue Organic Light Emitting Diodes with Ultralow Efficiency Roll‐Off

Abstract: Multi‐resonant thermally activated delayed fluorescent (MR‐TADF) materials are blooming for high‐resolution organic light‐emitting diodes (OLEDs). However, boron/nitrogen (B/N)‐integrated MR‐TADF emitters suffer severe efficiency roll‐off from their strong inter‐molecular π–π interactions. Herein, versatile narrowband pure blue emitters (mono‐mx‐CzDABNA and tri‐mx‐CzDABNA) are demonstrated featuring a ring‐fused extended π‐skeleton: a classic steric hindrance and rigidity accessed by integrating with meta‐xyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The stable surface morphology of the deposited films maintains the device efficiency. Additionally, the long intermolecular distances in host materials containing the bulky TPS group may prevent triplet-triplet annihilation (TTA) and/or singlet-triplet annihilation (STA), leading to increased EQE 29 .…”
Section: Resultsmentioning
confidence: 99%
“…The stable surface morphology of the deposited films maintains the device efficiency. Additionally, the long intermolecular distances in host materials containing the bulky TPS group may prevent triplet-triplet annihilation (TTA) and/or singlet-triplet annihilation (STA), leading to increased EQE 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Devices gave pure blue emission with l EL max 472 nm; CIE(0.13, 0.19), FWHM 34 nm and reduced efficiency roll-off with EQE max 26.9%; EQE 24.8% at 100 cd m À2 . 165 It is well established that MR emitters as TADF molecules can achieve high efficiency OLEDs with narrow-band emission. However, device durability can be limited because of the instability of triplet states due to the rather slow k RISC and long triplet lifetimes.…”
Section: Boron-containing Moleculesmentioning
confidence: 99%
“…Devices gave pure blue emission with λ EL max 472 nm; CIE(0.13, 0.19), FWHM 34 nm and reduced efficiency roll-off with EQE max 26.9%; EQE 24.8% at 100 cd m −2 . 165…”
Section: Multiresonance (Mr) Fused Carbazole Derivativesmentioning
confidence: 99%
“…Then Suh. et al reported two blue emitters mono - mx -CzDABNA and tri - mx -CzDABNA featuring the steric hindrance and rigidity accessed by the integration of ring-fused extended π-skeleton and meta -xylene rotors . Both the emitters showed blue emissions at 474 (fwhm = 34 nm) and 462 nm (fwhm = 26 nm) in toluene, and the corresponding devices exhibited emissions peaked at 481 (fwhm = 48 nm) and 472 nm (fwhm = 34 nm), and showed the maximum EQEs of 21.4 and 26.9%, respectively.…”
mentioning
confidence: 99%